Well-being in Finland: A comparison of municipalities and residential differentiation in two cities - Seppo Siirilä; Mari Vaattovaara; Ville Viljanen (Geographical Society of Finland, 2002)
Differences in well-being are examined at two regional levels. First, variations in well-being are studied based on municipal statistics by three indices that represent different aspects of life. The examination shows that the most problematic areas are in eastern and northern Finland. Second, residential differentiation is examined in two metropolitan areas, Helsinki and Tampere, through two variables: families with children and residents with university education. Metropolitan Helsinki is divided into socially distinctive residential areas. Low levels of education and the threat of unemployment concentrate in the northern and eastern parts of the city. Such clear socio-economic differentiation cannot be found in Metropolitan Tampere.